The Effect of Ultraviolet Exposure on the Quantity of Microplastics in the Air of Buildings Made from Plastic Waste - Nur Hilal; Teguh Widiyanto; Lagiono; Tri Marthy Mulyasari (Poltekkes Kemenkes Surabaya, 2024)
Microplastics are new environmental contaminants that result from plastic degradation and fragmentation. Ultraviolet is one of the physical factors that can affect plastic fragmentation. The study aimed to analyze the effect of ultraviolet exposure on microplastic levels in the air of buildings made from plastic waste materials and methods of true experiment research with posttest-only control group design. Air sampling was conducted 60 days in buildings made from plastic waste with treatment and control samples. Sampling of airborne microplastics by passive method. Visual observation of microplastics using a 10-fold magnification binocular microscope. Analysis of the effect of UV exposure on microplastic levels by simple linear regression. The results showed that the average level of microplastics in the air of buildings made from plastic waste in the treatment sample was 38.78 particles/m2/day, and in the control sample, 22 particles/m2/day. There are 3 forms of microplastics found in the air of buildings made from garbage, namely fragments, fibers, and films. Analysis of the effect of ultraviolet exposure on the quantity of microplastics in the air of buildings made from plastic waste obtained a p-value of 0.000<0.05. The study concludes that ultraviolet exposure affects microplastic levels in the air of buildings made from plastic waste.